2015
DOI: 10.1097/cmr.0000000000000134
|View full text |Cite
|
Sign up to set email alerts
|

Anchorage independency promoted tumor malignancy of melanoma cells under reattachment through elevated interleukin-8 and CXC chemokine receptor 1 expression

Abstract: Metastasis of melanoma cells during the recurrence or the late stage of melanoma has been characterized as the dissemination of tumor cells under anchorage independency. The secreted interleukin-8 (IL-8) and its conical receptors from melanoma cells have been associated with melanoma malignancy. However, their correlations with melanoma cells under anchorage independency were unclear. Suspension of adherent melanoma cells generated the suspended melanoma cell model of anoikis resistance. The in-vivo xenograft … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…Indeed, both IL8 and CCL2 act as a tumor autocrine growth factors increasing melanoma cell migration in metastatic lesions (39,40). Thus, it is conceivable to speculate that these NK cell subsets may be able to migrate to the early melanoma metastatic foci.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, both IL8 and CCL2 act as a tumor autocrine growth factors increasing melanoma cell migration in metastatic lesions (39,40). Thus, it is conceivable to speculate that these NK cell subsets may be able to migrate to the early melanoma metastatic foci.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they could also have a direct effect in enhancing motor abilities and chemotaxis in tumor cells, as well as having indirect effect in promoting angiogenesis and the digestion of the extracellular matrix to promote tumor growth and metastasis by stimulating tumor growth [ 10 ]. It has been reported [ 11 14 ] that the use of CXCR1/CXCR2-specific antibodies in vitro can inhibit melanoma tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…In recent research studies, IL-8, an intense studied proangiogenic factor, was reported as one of the cytokines secreted by melanoma cells, influencing thus the differentiation pattern of keratinocytes and being a factor that mediates intercellular interactions in melanoma [ 32 ]. Moreover, it was shown that elevated IL-8 secretion and change in CXCR expression enhance melanoma malignancy [ 33 ]. Results performed in several solid cancers showed that serum IL-8 indicates tumor burden and prognosis in melanoma as well [ 34 ].…”
Section: Discussionmentioning
confidence: 99%